(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented at Pondok Pesantren Quantum Idea, Bekasi, with the goal of equipping students with essential skills in electric welding using the Shielded Metal Arc Welding (SMAW) method and foundational electrical safety. The program addressed key issues such as limited access to vocational education, inadequate safety awareness, lack of proper facilities, and the absence of technical integration into students’ economic independence. The program implemented four main stages: socialization, procurement of welding equipment and safety gear, hands-on SMAW welding training, and entrepreneurship development. The results showed a significant improvement in students’ technical knowledge, practical welding abilities, and awareness of occupational health and safety (OHS). The students were also able to install basic electrical systems and perform safe maintenance practices. Furthermore, participants demonstrated increased motivation to use their newly acquired skills for entrepreneurial ventures, such as establishing small-scale welding workshops within the pesantren. The program successfully fostered a culture of technical independence and safe work practices, aligning with the pesantren’s long-term vision of empowering students with real-world industrial competencies while preserving Islamic values.